2017
DOI: 10.1021/acs.iecr.7b03316
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic and ab Initio Investigation of Aqueous Boric Acid, Borate, and Polyborate Speciation from 25 to 80 °C

Abstract: Temperature-dependent Raman studies of the aqueous speciation of boric acid and sodium borate have been carried out at 25 and 80 °C. Normalized solvent-corrected reduced isotropic Raman spectra were obtained from perpendicular and parallel polarization measurements using perchlorate anion, [ClO4]−, as an internal standard. The intensity variations of these bands with concentration and temperature provided strong evidence that these arise from boric acid B­(OH)3, borate [B­(OH)4]−, and the polyborate species [B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 53 publications
10
73
1
Order By: Relevance
“…The Mulliken charges of B (1) and B (3) are nearly equal as shown in Table 1. The Mulliken charges of O (9) and O (12) are equal, and these values are more negative than those of O (5) and O (8) . Thus, it can be inferred that the OH of water molecules tends to bond to B (1) and B (3) and that H preferentially bonds to O (9) and O (12) during hydrolysis reaction.…”
Section: Atomsmentioning
confidence: 91%
See 4 more Smart Citations
“…The Mulliken charges of B (1) and B (3) are nearly equal as shown in Table 1. The Mulliken charges of O (9) and O (12) are equal, and these values are more negative than those of O (5) and O (8) . Thus, it can be inferred that the OH of water molecules tends to bond to B (1) and B (3) and that H preferentially bonds to O (9) and O (12) during hydrolysis reaction.…”
Section: Atomsmentioning
confidence: 91%
“…In pathway A, a water molecule attacks to B (3) 4 2− ] to form dihydrogen bond, and this makes the structure more stable. The more negative ESP near BO 4 and the more negative Mulliken charges of O (9) and O (12) may be the reasons for forming dihydrogen bonds. Cheng et al studied the hydrolysis mechanisms of aluminum alkoxide Al(OR) 3 and found that two hydrogen atoms of water first bond to the oxygen atoms of OR group in the form of hydrogen bond to form intermediate product.…”
Section: Atomsmentioning
confidence: 99%
See 3 more Smart Citations